CLIMATE LITERACY AWARENESS AMONG PRESERVICE TEACHERS IN MALAYSIA - Nasir Nayan; Hanifah Mahat; Mohmadisa Hashim; Yazid Saleh; Saiyidatina Balkhis Norkhaidi (LPMPP Universitas Negeri Yogyakarta, 2020)
Climate change and global warming are the primary issues often debated when environmental issues are discussed nowadays. Among the efforts made to raise awareness concerning mitigation and adaptation to climate change is climate literacy acquired from the educational medium. Therefore, this article seeks to identify the level of awareness on climate literacy among preservice teachers in Malaysia. This study involved 500 final-year students from nine faculties at Sultan Idris Education University using the stratified sampling method. A questionnaire instrument was used to get feedback, containing four study variables, namely the knowledge, attitudes, skills, and practices of climate change mitigation and adaptation. The findings showed that the knowledge of and attitudes towards climate change mitigation and adaptation variables were at high levels, while the skills and practices of climate change mitigation and adaptation variables were at moderate levels. Thus, this indicates that students’ knowledge of and attitudes towards climate change mitigation and adaptation were good and satisfactory, but not the skills and practices of climate change mitigation and adaptation, which were still moderate and could be improved over time. The findings and issues that have been studied can be used as a reference and guide for universities, educators and ministries in improving students’ climate literacy, aiming for a more sustainable life.